Effects of Pressure and Temperature on Well Cement Degradation by Supercritical CO2 - Sauki, Arina (IJENS Publishers, 2010)
The overall objective of this study was to investigate the physical and chemical effects of supercritical CO2 attack on well cement at different temperature and pressure condition. The dissimilarity of attack was compared in twoexposure conditions i.e. CO2-saturated brine and wet supercritical CO2. Type of cement used for this invent was neat cement, Class G and was prepared according to API recommended practice 10B-2 by using Constant Speed Mixer. Curing of cement slurry and CO2 exposure test were done by using Curing Chamber and Cement Autoclave. Measurement and evolution of cement alteration against CO2 attack was determined under various temperatures and pressure condition at different exposure duration. Results from BackScattered Electron of Scanning Electron Microscopy (BSE-SEM), Energydispersive X-Ray Spectroscopy (EDX), X-Ray Diffraction (XRD) and compressive strength tester was analysed and studied. At high temperature, 1200C, cement will lose its strength faster than lower temperature, 400C. Same goes to pressure, the strength will lose faster in higher pressure, 140 bar as compared to lower pressure, 105 bar. Faster reduction in strength was found in CO2- saturated brine exposure compared to wet supercritical CO2. Index Terms – Supercritical CO2, brine, alteration, compressive strength, curing.